Social inclusion and intellectual disability in Ireland: social inclusion co-ordinators' perspectives on barriers and opportunities - Antonia Kenny; Martin Power (Scottish Journal of Residential Child Care)
Social inclusion is a cornerstone of policy for individuals with disabilities. Yet, studies have shown that in spite of positive developments, meaningful social inclusion remains a challenge. In Ireland, a number of policies have been enacted in recent years to promote social inclusion. In 2011, 'Time to move from congregated settings – A strategy for community inclusion' (2011), was introduced and sought to move individuals from congregated settings into the community. This was quickly followed by 'New Directions' (2012), which promoted the use of community supports to expand choice and inclusion. Implementation however has confronted a number of challenges. Against this backdrop, this study explored social inclusion co-ordinators' perspectives of social inclusion, barriers and facilitators. Two semi-structured group interviews were conducted with eleven co-ordinators in two day services. These co-ordinators have a particular remit to promote social inclusion in the day service they work in. The interviews were analysed thematically and two key themes emerged: a disconnect between the policy goals and lived experience, and barriers to meaningful social inclusion.